2020
DOI: 10.1002/jbt.22641
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting endoplasmic reticulum stress by activation of G‐protein‐coupled estrogen receptor to protect retinal astrocytes under hyperoxia

Abstract: Retinal vascularization is arrested at the early (hyperoxia) stage in retinopathy of prematurity (ROP), a leading cause of blindness in children. Estrogen was reported to alleviate ROP by inhibiting reactive oxygen species, the upstream signaling molecules of endoplasmic reticulum stress (ERS). Astrocytes have long been proposed to guide angiogenesis, because they form a reticular network that provides a substrate for migrating endothelial cells. However, the factors that control the vascularization of the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Its presence has been demonstrated in various areas of the body (e.g., the reproductive, nervous, endocrine, immune and cardiovascular systems) and in the retina. [10,11] Evidence has been reported that GPER-1 plays a crucial role in metabolic regulation (lipids and glucose homeostasis, insulin production and action, etc. ), blood pressure, and immune functions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Its presence has been demonstrated in various areas of the body (e.g., the reproductive, nervous, endocrine, immune and cardiovascular systems) and in the retina. [10,11] Evidence has been reported that GPER-1 plays a crucial role in metabolic regulation (lipids and glucose homeostasis, insulin production and action, etc. ), blood pressure, and immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…), blood pressure, and immune functions. [9,10,18] Previous studies indicate that GPER-1 activation increases the e ciency of glucose transporters, reduces oxidative stress products, and regulates the in ammatory response; thus, it plays a neuroprotective role. [1,[11][12] In diabetic patients, the oxidant/antioxidant balance changes in favour of oxidation due to increased oxidative stress in the body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations